Aplicación de una técnica de trasplante a un Coleoptero - Cruz Rosales, Magdalena (Instituto de Ecología, A.C., 1994)
A simple transplant technique in a beetle is described. Application of this technique does not promote serious disturbance to the receptor which recover rapidly.